PENGARUH LIKUIDITAS, RISIKO BISNIS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Roshidayah Roshidayah; Anita Wijayanti; Suhendro Suhendro (Jurnal Proaksi, 2021)
This study aims to examine and analyze the effect of liquidity, business risk, and company growth on dividend policy in property and real estate companies in 2015-2019 listed on the Indonesia Stock Exchange (BEI). The method used in this research is quantitative method. Sampling was done by purposive sampling was done by purposive sampling through several criteria, in order to obtain a sampling through several criteria, in order to obtain a sample of 46 companies. Hypothesis testing using multiple linear regression method. The results showed that the liquidity variable and business risk variables had an effect on dividend policy, but the company growth variable showed that the resuts had no effect on dividend policy. Keywords : Liquidity, Business Risk, Company Growth, Dividend Policy